2008
DOI: 10.1111/j.1365-2605.2008.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology of sperm protamine abnormalities and their potential impact on the sperm epigenome

Abstract: During the elongating spermatid stage of spermatogenesis, there is a step-wise replacement of nuclear histones with protamines 1 and 2. In fertile men, the ratio of protamine 1/protamine 2 (P1/P2) is within the narrow range of 0.8-1.2. Ratios above or below that range are associated with infertility, exhibiting a wide range of defects including decreased sperm counts, morphology, fertilization ability, and embryo implantation capacity. In this review, we highlight studies evaluating potential causes of abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 92 publications
0
52
0
Order By: Relevance
“…On the contrary, apoptosis of both spermatocytes and spermatids significantly increased with increasing TSA doses, suggesting for an inhibitory role of TSA mainly on meiosis but not mitosis [75,76]. During spermatogenesis, methylation of H3K and H4K histone tails is regulated by histone methyltransferases (HTM) and histone demethylases (HDM) [77,78]. Acetylation of H2A, H2B, H3, and H4 was shown to be high in mouse spermatogonia, and these histones were deacetylated throughout meiosis in round spermatids and reacetylated in elongating spermatids [72] (Fig.…”
Section: Role Of Histone Modifications In Male Infertilitymentioning
confidence: 99%
“…On the contrary, apoptosis of both spermatocytes and spermatids significantly increased with increasing TSA doses, suggesting for an inhibitory role of TSA mainly on meiosis but not mitosis [75,76]. During spermatogenesis, methylation of H3K and H4K histone tails is regulated by histone methyltransferases (HTM) and histone demethylases (HDM) [77,78]. Acetylation of H2A, H2B, H3, and H4 was shown to be high in mouse spermatogonia, and these histones were deacetylated throughout meiosis in round spermatids and reacetylated in elongating spermatids [72] (Fig.…”
Section: Role Of Histone Modifications In Male Infertilitymentioning
confidence: 99%
“…The spermatozoon is a specialized cell with a condensed nucleus, in which the majority of the DNA is tightly packaged in toroidal structures by protamines (Oliva & Dixon, 1991;Oliva, 2006;Balhorn, 2007;Carrell et al, 2008;Oliva & Castillo 2011). In mice as well as humans, there are two types of protamines: protamine 1 (P1) and protamine 2 (P2).…”
Section: Introductionmentioning
confidence: 99%
“…In mice as well as humans, there are two types of protamines: protamine 1 (P1) and protamine 2 (P2). Several studies have reported an altered amount of protamines in the sperm cell of infertile patients and a correlation with DNA fragmentation (Corzett et al, 2002;Oliva, 2006;Balhorn, 2007;Carrell et al, 2008;de Mateo et al, 2009). Furthermore, haploinsufficiency of only one of the protamine 1 gene (Prm1) or protamine 2 gene (Prm2) alleles in knockout mice models results in severely altered spermatogenesis, increased DNA damage and sperm cell apoptosis (Cho et al, 2001(Cho et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…According to this hypothesis the first step in the DNA damage cascade has its origins in spermiogenesis when the DNA is being remodelled prior to condensation. Defects in the chromatin remodelling process result in the production of spermatozoa that are characterized by an overall reduction in the efficiency of protamination, an abnormal protamine1 to protamine2 ratio and relatively high nucleohistone content [30,36,37]. These defects in the chromatin remodelling process create a state of vulnerability, whereby the spermatozoa become susceptible to oxidative damage.…”
Section: Mitochondria and Rosmentioning
confidence: 99%